An Eco-efficiency Analysis of Space Agencies Launching Activities - Massimo Finocchiaro Castro; Calogero Guccio; Domenica Romeo (ZBW - Leibniz Information Centre for Economics, 2021)
In the last few years, countries and commercial firms are increasingly interested in space activities for civil, military, and commercial purposes (Undseth et al., 2020). As it has been shown in NASA report (2019), investment in space program drives to significant economic benefits to the whole society. We propose the first methodological paper to empirically study the efficiency of satellite launches employing the Data Envelopment Analysis input-oriented technique. We show that overall average efficiency is quite low and that it can significantly be improved by studying subsamples of DMUs according to user, purpose, and class of orbit. The most relevant results can be achieved in the communications purpose cluster where the bias corrected efficiency scores tripled with respect to average efficiency level reached by overall estimates. Hence, the scope of satellites seems to affect the mission efficiency and, even more relevant, the future creation of debris.
Keywords: D24; Q53; R41; 330; efficiency; space programs; debris; space agencies; satellites